Amyloid Peptide Induced Neuroinflammation Increases the P2X7 Receptor Expression in Microglial Cells, Impacting on Its Functionality - Martínez-Frailes, Carlos; Di Lauro, Caterina; Bianchi, Carolina; de Diego-García, Laura; Sebastián-Serrano, Álvaro; Boscá, Lisardo; Díaz-Hernández, Miguel (Frontiers in Cellular Neuroscience, 2019)
Alzheimer disease is a neurodegenerative disease characterized by the presence of senile plaques composed of amyloid-β (Aβ) peptide, neurofibrillary tangles, neuronal loss and neuroinflammation. Previous works have revealed that extracellular ATP, through its selective receptor P2X7 (P2X7R), is essential to neuroinflammation and neurotoxicity induced by Aβ. P2X7R is upregulated on microglial cells around the senile plaques. This upregulation progressively rises with age and is parallel with an accumulation of senile plaques and also correlates with the synaptic toxicity detected both in animal models reproducing AD and human patients of AD. Furthermore, the late onset of the first AD-associated symptoms suggests that aging associated-changes may be relevant to the disease progression. Thus, microglia motility and its capacity to respond to exogenous ATP stimulus decrease with aging. To evaluate whether the P2X7R age related-changes on microglia cells may be relevant to the AD progression, we generated a new transgenic mouse model crossing an Aβ peptide mouse model, J20 mice and the P2X7R reporter mice P2X7REGFP. Our results indicate that neuroinflammation induced by Aβ peptide causes changes in the P2X7R distribution pattern, increasing its expression in microglial cells at advanced and late stages, when microgliosis occurs, but not in the early stages, in the absence of microgliosis. In addition, we found that P2X7R activation promotes microglial cells migration to senile plaques but decreases their phagocytic capacity. Moreover, we found a significant reduction of P2X7R transcription on neuronal cells at the early and advanced stages, but not at the late stages. Since previous studies have reported that either pharmacological inhibition or selective downregulation of P2X7R significantly improve behavioral alterations and reduce the incidence and size of senile plaques in the early and advanced stages of AD, the results presented here provide new evidence, indicating that this therapeutic approach could be also efficient in the late stages of the disease.